Managing customer service through artificial intelligence-driven chatbot systems in Islamic Banking institutions - Wahyuni, Eka Sri; Yuningsih, Ayu; Arisandy, Yosy (Universitas Negeri Surabaya, 2025)
This study examines the implementation of chatbots in Bank Syariah Indonesia (BSI) to enhance customer service in the Islamic banking sector. This study used a literature review in collecting and analyzing the secondary data in the form of papers downloaded from Google Scholar, Scispace, DOAJ, and Scopus websites. There were 26 papers gathered as samples of this study from 2015-2024. The data were analyzed through systematic data reduction, presentation, and conclusion-drawing. The findings show that deploying chatbots can significantly improve service delivery by reducing operational workloads through quick replies to repetitive customer inquiries. Chatbots serve as an innovative solution that handles routine questions swiftly, thereby increasing efficiency and allowing staff to focus on more complex tasks. Their continuous, round-the-clock availability further enhances customer engagement and experience by providing immediate assistance at any time, eliminating extended waiting times for information. Additionally, the chatbot’s ability to interpret customer interactions provides valuable insights into customer behavior and preferences. Such insights enable BSI to better understand about customer needs and identify usage patterns of Sharia-compliant banking products. However, the implementation of chatbots in Islamic banking also requires careful consideration of Islamic ethics. The development of AI must integrate maqasid al-shariah values such as justice, transparency, and data protection to ensure alignment between technological efficiency and Shariah principles.